2013
DOI: 10.1093/europace/eut049
|View full text |Cite
|
Sign up to set email alerts
|

True complete left bundle branch block morphology strongly predicts good response to cardiac resynchronization therapy

Abstract: In patients with conventional wider LBBB morphology, the presence of mid-QRS notching or slurring is a strong predictor of better response to CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 36 publications
2
55
1
3
Order By: Relevance
“…These include the general evidence of LV conduction delay; QS or rS (in V1 and V2) and QRS duration ≥ 140 ms (males) or ≥ 130 ms (females), and specific evidence of LBBB with mid-QRS notch or slur in two or more of the following leads: V1, V2, V5, V6, I and aVL (Appendix 1). Recent studies have shown that consideration of Strauss criteria [2] and other strict LBBB criteria [11][12][13], sharing the QRS morphology criteria of the Strauss criteria, significantly improves prediction of CRT response and clinical outcome. Furthermore, Strauss criteria increase the specificity of complete LBBB diagnosis in the presence of LV hypertrophy/dilatation and incomplete LBBB [14].…”
Section: Introductionmentioning
confidence: 99%
“…These include the general evidence of LV conduction delay; QS or rS (in V1 and V2) and QRS duration ≥ 140 ms (males) or ≥ 130 ms (females), and specific evidence of LBBB with mid-QRS notch or slur in two or more of the following leads: V1, V2, V5, V6, I and aVL (Appendix 1). Recent studies have shown that consideration of Strauss criteria [2] and other strict LBBB criteria [11][12][13], sharing the QRS morphology criteria of the Strauss criteria, significantly improves prediction of CRT response and clinical outcome. Furthermore, Strauss criteria increase the specificity of complete LBBB diagnosis in the presence of LV hypertrophy/dilatation and incomplete LBBB [14].…”
Section: Introductionmentioning
confidence: 99%
“…Under the current criteria, approximately 30% of patients undergoing CRT are nonresponders, and improving on these criteria is an active field of research [11]. One factor influencing CRT response is the presence of strict left bundle-branch block (LBBB), defined by a longer QRS duration (≥ 140ms in men and ≥ 130ms in women) and a mid-QRS notching [19], and characterised by dyssynchronous contraction of the septum relative to the LV lateral wall. While LBBB has a characteristic large-scale motion abnormality, it is yet unknown whether there is a particular scale of cardiac motion that distinguishes CRT responders' hearts from those of non-responders.…”
Section: Clinical Datamentioning
confidence: 99%
“…Patients in the CRT-D arm experienced a 34 % reduction in the combined endpoint of HF or death. The study pre-specified an analysis by gender and found that the primary outcome of HF or death was seen in11 % of those with CRT-D compared with 20 [12].…”
Section: Gender Differences In the Outcome Of Large Clinical Trialsmentioning
confidence: 99%
“…New gender-specific strict LBBB criteria were proposed that require a QRS of 130 milliseconds or longer in women and 140 milliseconds or longer in men, along with mid-QRS notching and/or slurring [18]. Recent single-center studies demonstrated that patients not meeting strict LBBB criteria had a 4-fold higher rate of heart failure hospitalization or death and did not respond to CRT-D compared with patients who met the strict LBBB criteria [19,20]. Patients without LBBB receiving CRT-D had a lower mortality risk than non-LBBBICD patients, although the difference was small (absolute risk difference of 2% in men and 3% in women) [21].…”
Section: Gender Differences In Lbbb Occurrence and New Gender-specifimentioning
confidence: 99%